Combining impregnation and co-pyrolysis to reduce the environmental risk of biochar derived from sewage sludge. (March 2022) - Min, Xue; Ge, Tao; Li, Hui; Shi, Yanhong; Fang, Ting; Sheng, Bixuan; Li, Huaiyan; Dong, Xinju
Abstract: Sewage sludge derived biochar has great potential for agricultural application, whereas the risk of heavy metals in sewage sludge is a key challenge for utilization. This study investigated the synergetic effect of co-pyrolysis and ZnCl2 impregnation treatment on the surface characteristics and potential ecological risk of heavy metals in sewage sludge derived biochar. It was concluded that ZnCl2 impregnation led to an increase in biochar yield, O and S content, but decrease the ash content and pH. Additionally, the thermal stability of ZnCl2 -added biochar was decreased. Semi-quantitive specific functional groups analysis suggested that ZnCl2 impregnation had a negative effect on the content of CO and C-O, while promoted the formation of aromatic CC. And the functional group of CO was retained in biochar by co-pyrolysis with Camellia oleifera shell due to its high content of potassium. For heavy metal passivation, ZnCl2 impregnation decreased total content of heavy metals by chlorination, while the oxidizable fraction (F3) of heavy metals showed an increasing tendency. Results of potential ecological risk assessment indicated that combining ZnCl2 impregnation and co-pyrolysis had great potential to reduce the ecological risk of heavy metals in sewage sludge derived biochar. Graphical abstract: Image 1 Highlights: Surface characteristics of biochar with different treatment were analyzed. ZnCl2 impregnation had a significant effect on biochar properties. ZnCl2 impregnation and co-pyrolysis can reduce the ecological risk from heavy metals in biochar.